CCR5 chemokine receptor gene polymorphisms in ocular toxoplasmosis - de Faria Junior, Geraldo M.; Ayo, Christiane M.; de Oliveira, Amanda P.; Lopes, Alessandro G. [UNESP]; Frederico, Fábio B.; Silveira-Carvalho, Aparecida P.; Previato, Mariana; Barbosa, Amanda P.; Murata, Fernando H.A.; de Almeida Junior, Gildásio Castello; Siqueira, Rubens Camargo; de Mattos, Luiz C.; et al. (Elsevier, 2018)
C–C chemokine receptor type 5 (CCR5) is a chemokine receptor that influences the immune response to infectious and parasitic diseases. This study aimed to determine whether the CCR5Δ32 and CCR5 59029 A/G polymorphisms are associated with the development of ocular toxoplasmosis in humans. Patients with positive serology for Toxoplasma gondii were analyzed and grouped as ‘with ocular toxoplasmosis’ (G1: n = 160) or ‘without ocular toxoplasmosis’ (G2: n = 160). A control group (G3) consisted of 160 individuals with negative serology. The characterization of the CCR5Δ32 and CCR5 59029 A/G polymorphisms was by PCR and by PCR-RFLP, respectively. The difference between the groups with respect to the mean age (G1: mean age: 47.3, SD ± 19.3, median: 46 [range: 18–95]; G2: mean age: 61.3, SD ± 13.7, median: 61 [range: 21–87]; G3: mean age: 38.8, SD ± 17.9, median: 34 [range: 18–80]) was statistically significant (G1 vs.G2: p-value <0.0001; t = 7.21; DF = 318; G1 vs.G3: p-value <0.0001; t = 4.32; DF = 318; G2 vs. G3: p-value <0.0001; t = 9.62; DF = 318). The Nagelkerke r2 value was 0.040. There were statistically significant differences for the CCR5/CCR5 (p-value = 0.008; OR = 0.261), AA (p-value = 0.007; OR = 2.974) and AG genotypes (p-value = 0.018; OR = 2.447) between G1 and G2. Individuals with the CCR5/CCR5 genotype and simultaneously the CCR5-59029 AA or AG genotypes have a greater risk of developing ocular toxoplasmosis (4% greater), which may be associated with a strong and persistent inflammatory response in ocular tissue.
Keywords: CCR5 receptor; Chemokines; Genetic polymorphism; Ocular toxoplasmosis; Toxoplasma gondii